Unstable thoracolumbar injuries: A bibliometric analysis of the most influential papers - Eduardo Cattapan Piovesan; Werner Petry Silva; Alfredo Guiroy; Bruna Zanatta De Freitas; Vinícius Cercena Vargas; Charles Carazzo (Journal of Craniovertebral Junction and Spine)
Background: Bibliometric analyses are a proficient method for understanding the dynamics of publications. Unstable thoracolumbar injuries are a prevalent topic in neurosurgery and orthopedic research. Methodology: Web of Science was searched for the 100 most-cited articles on unstable thoracolumbar injuries. A number of citations, article title, first author’s name, year and journal of publication and its impact factor (IF), specialty, affiliation, country of the first author, and type of the article were retrieved. Results: The articles were published in 32 different journals from 1977 to 2020. Spine (38 articles in the top 100 and 3694 citations) was the journal with the greatest number of articles and citations, and the highest number of primary research papers (31 articles, accounting for 2915 citations). The United States was the country with the most articles (45) and citations (4541). The University of California (5 articles, 6 primary research, and 781 citations) was the institution with the highest number of citations, articles, and primary research articles. Orthopedic was the specialty with the most significant number of publications and the most cited (77 articles and 7197 citations). The first author with the greatest number of publications and primary research articles was R. F. McLain (4 articles, being 3 primary research, and 646 citations), while the most cited was A. R. Vaccaro (3 articles and 695 citations). Eighty publications were primary and 20 were secondary research. Conclusions: The unstable thoracolumbar research field is prominent in North America and has been more frequently published in orthopedic journals, after 1995.